The Development of Tourism Towards Poverty Alleviation in Batu City - Yeni Astiyanti; Candra Fajri Ananda; Moh Khusaini (Institute of Research and Community Service, University of Brawijaya, 2020)
The purpose of the tourism development is to reduce poverty and unemployment. Tourism sector in Batu City is increasingly characterized by an increasing the number of tourism destinations and the tourists. Tourism in Batu City is developed through capital and community base have some impacts to the development. In 2014, there was a decrease in poverty rate by 12,28%, while the amount of unemployment in Batu City increased by 0,11%. The due to aims of this research are to analyze the development of tourism in Batu City so did how its impact to the poverty in this city is using Partial Least Square Analysis. Based on the result of the analysis is known that the development of tourism in Batu City categorized as consolidation phase. The other result is tourism development due to both capital and community based is still not able to reduce poverty significantly. The development has provided more benefit is creating employment and higher impact comes from community-based tourism. The development of tourism in Batu City to further prioritize community-based tourism so that people can directly get the impact of tourism development.